2022
DOI: 10.1371/journal.pone.0268017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with hepatorenal tyrosinemia from a single Egyptian center

Abstract: Although very recently, in Egypt, sick newborn screening has included screening for hepatorenal tyrosinemia, yet, it is not yet included in nationwide neonatal screening and hence diagnosis may be delayed. The aim of this study was to analyze data of all cases presenting with hepatorenal tyrosinemia to the Pediatric Hepatology Unit, Cairo University, Egypt from 2006 to 2019. Data were retrieved from patients’ files including age of onset of symptoms, clinical signs, blood counts, liver functions, serum phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Long-term administration of nitisinone (2-(2-nitro-4-3 trifluoromethylbenzoyl)-1,3-cyclohexanedione-NTBC), a well-established therapy for patients with type I tyrosinemia, is recommended. NTBC reduces the risk of HCC and porphyria attacks and leads to a decrease in AFP levels [19,20]. However, Bhushan et al observed in their patient cases that even with long-term NTBC therapy and normalization of AFP, the risk of HCC is not completely eliminated [16,21].…”
Section: Type I Tyrosinemiamentioning
confidence: 97%
See 1 more Smart Citation
“…Long-term administration of nitisinone (2-(2-nitro-4-3 trifluoromethylbenzoyl)-1,3-cyclohexanedione-NTBC), a well-established therapy for patients with type I tyrosinemia, is recommended. NTBC reduces the risk of HCC and porphyria attacks and leads to a decrease in AFP levels [19,20]. However, Bhushan et al observed in their patient cases that even with long-term NTBC therapy and normalization of AFP, the risk of HCC is not completely eliminated [16,21].…”
Section: Type I Tyrosinemiamentioning
confidence: 97%
“…Studies have shown that other bone marrow disorders with a genetic basis, such as Blackfan-Diamond syndrome, Shwachman-Diamond anemia, or congenital dyskeratosis congenital, exhibit normal AFP levels [36]. Until recently, AFP was used as a simple diagnostic tool for Fanconi anemia (FA), with studies indicating varied sensitivity: 93% sensitivity and 100% specificity (Cassinat et al, 2000) [37]; 46% sensitivity (Aslan et al, 2002) [19]; and 71% sensitivity (Salem et al, 2019) [17]. However, a recent study by Alter et al suggests a sensitivity of approximately 25%, although their study included a group of FA patients with a higher median age [36].…”
Section: Hematopoietic System Fanconi Anemiamentioning
confidence: 99%